2010
DOI: 10.1002/pola.23990
|View full text |Cite
|
Sign up to set email alerts
|

Initiating electropolymerization on graphene sheets in graphite oxide structure

Abstract: Because of its special chemical composition, graphite oxide has peculiar influences on electrochemical processes. The existence of various functional groups significantly affects electropolymerization processes and the formation of conductive polymers. Electrochemical synthesis of polyaniline (as a prototype of conductive polymers) on a paste‐based substrate of graphite oxide was investigated. In this case, the electropolymerization is significantly different from conventional cases, and the polymer is generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Therefore, it is important to modify RG‐O platelets to be an appropriate form for hybridization with conducting polymers and realization of synergistic effects on electrical properties. To this end, several reports have shown the combined effects of RG‐O and conducting polymers for various applications,20–24 some of which have detailed specific types of RG‐O/conducting polymer composites such as composites of RG‐O and poly(3,4‐ethylenedioxythiophene) (PEDOT) 25, 26…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to modify RG‐O platelets to be an appropriate form for hybridization with conducting polymers and realization of synergistic effects on electrical properties. To this end, several reports have shown the combined effects of RG‐O and conducting polymers for various applications,20–24 some of which have detailed specific types of RG‐O/conducting polymer composites such as composites of RG‐O and poly(3,4‐ethylenedioxythiophene) (PEDOT) 25, 26…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical behavior during the electropolymerization of β‐CD on GCE/rGO was studied, since the voltammetric profile are used to control the electropolymerization process and the growth of the polymer film . The electropolymerization was performed by successive cyclic voltammograms (50 cycles) on GCE surface in the potential range between −2.0 and +2.2 V. The voltammograms obtained during the β‐CD electropolymerization on GCE/rGO are in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that the morphology of the prepared composites was influenced dramatically by the different mass ratios of the functional graphene [11,14,16,22,38]. The effect of dopant on morphology formation in graphene/conductive polymer nanocomposites was also investigated with graphite nanoplatelet as support.…”
Section: Introductionmentioning
confidence: 96%